Analysis of Physical Hydro-Oceanographic Factors for Abrasion at Pasir Jambak Beach, Padang City, West Sumatra Province - Athhary, Dhiva Danaya; Rifardi, Rifardi; Elizal, Elizal (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2023)
Abrasion is a common problem in coastal areas. This is due to natural factors that influence the phenomenon of abrasion in a coastal area, including the hydro-oceanographic processes that take place in the sea. Pasir Jambak Beach is one of the beaches in Padang City that is experiencing worrying abrasion. Therefore, it is necessary to research the analysis of physical hydro-oceanographic factors for beach abrasion. This survey was conducted in February - April 2023 at Pasir Jambak Beach. This study aimed to determine the degree of abrasion and its relationship to the hydro-oceanographic physics of the beach. The method used is survey and purposive sampling. The data obtained were tabulated and descriptively quantitatively analyzed by multiple linear regression. The results showed that the beach experienced a dominant abrasion process in the period 1995-2023 compared to accretion with an abrasion rate of 77.94%. The highest average wear rate occurred in 2019-2023 of 3.86 m/year and the lowest in 2003-2007 of 1.9 m/year. Physical hydro-oceanographic factors at Pasir Jambak Beach have a significant influence on the abrasion phenomenon that occurs.